New blend of renewable bioplastic based on starch and acetylated xylan with high resistance to oil and water vapor - Martins, Julia Ribeiro [UNESP]; Llanos, Jaiber Humberto Rodriguez [UNESP]; Abe, Mateus Manabu [UNESP]; Costa, Michelle Leali [UNESP]; Brienzo, Michel [UNESP] (Elsevier, 2024)
Renewable materials of biological origin exhibit attractive properties in relation to traditional plastics, as they can be partially or completely replaced, thereby reducing environmental impacts. Hemicelluloses are a group of polysaccharides that have expanded applications when acetylated. Acetylation can improve the mechanical strength and water vapor barrier properties of xylan-based bioplastics. By partially acetylating xylan in the present study, it was possible to use water as a solvent for the film-forming solution and starch as a second polysaccharide in the formation of bioplastics. Xylan was modified via partial chemical acetylation by varying the reaction time, solvent, and catalyst content. The bioplastics were formed by non-acetylated xylan and acetylated xylan with degrees of substitution (DS) of 0.45 and 0.9, respectively, with starch to form blends using glycerol as a plasticizer. Acetylation with DS 0.45 showed better results in increasing the hydrophilicity of the bioplastic. On the other hand, acetylation influenced the thermal stability of bioplastics, increasing the maximum temperature of the degradation rate from 302 °C to 329 °C and 315 °C, owing to changes in the crystallinity of the polymers. In addition to the modulus of elasticity 2.99 to 290.61 and 274.67 MPa for the non-acetylated bioplastic and the bioplastic with DS of 0.45 and 0.90, respectively. Thus, the films obtained presented suitable physicochemical properties for use in various industrial applications, such as active and intelligent packaging in the food sector.
Keywords: Acetylation; Chemical modification; Sugarcane bagasse; Water-soluble; Xylan